2002
DOI: 10.1038/modpathol.3880508
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of MYCN, DDX1, and NAG Gene Copy Number in Neuroblastoma Using a Real-Time Quantitative PCR Assay

Abstract: Amplification of the proto-oncogene MYCN is a strong adverse prognostic factor in neuroblastoma patients in all tumor stages. The status of the MYCN gene has become an important factor in clinical decision making and therapy stratification. Consequently, fast and accurate assessment of MYCN gene copy number is of the utmost importance and the use of two independent methods to determine MYCN status is recommended. For these reasons we have developed and evaluated a real-time quantitative PCR (Q-PCR) assay as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 22 publications
4
108
0
Order By: Relevance
“…Moreover, during the evaluation process, we managed to visually discern the concentration of MYCN, facilitating its semi-quantification without the need for densitometry. Consistent with the results of a previous study (8), our results from the absolute and relative real-time quantification of MYCN from tumor samples were identical. Comparison of real-time quantitative PCR with SQ-PCR demonstrated that both assays perform equally well in determining MYCN molecule number and that the SQ-PCR method defined MYCN molecule number with an accuracy approaching that of real-time quantitative PCR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, during the evaluation process, we managed to visually discern the concentration of MYCN, facilitating its semi-quantification without the need for densitometry. Consistent with the results of a previous study (8), our results from the absolute and relative real-time quantification of MYCN from tumor samples were identical. Comparison of real-time quantitative PCR with SQ-PCR demonstrated that both assays perform equally well in determining MYCN molecule number and that the SQ-PCR method defined MYCN molecule number with an accuracy approaching that of real-time quantitative PCR.…”
Section: Discussionsupporting
confidence: 92%
“…We also evaluated the relative quantification power of the test by calculating the MYCN molecules based on the observed C T values. This was done by transforming the difference in C T values between the tumor sample and the calibrator to a copy number ratio (8).…”
Section: Methodsmentioning
confidence: 99%
“…Frequently, adjacent or more distantly located genes, such as DDX1, NAG, and ALK, are coamplified with MYCN, but amplification events in the absence of MYCN amplification are rare. Whether these coamplifications have a prognostic impact awaits clarification (Manohar et al, 1995;Squire et al, 1995;George et al, 1997;De Preter et al, 2002;Weber et al, 2004).…”
Section: Genetic Features Of Neuroblastic Tumours Associated With Unfmentioning
confidence: 99%
“…The real-time RT-PCR cycle started with the initial denaturation at 951C for 10 min, followed by 45 cycles of denaturation at 951C for 10 s, annealing at 611C for 10 s, and elongation at 721C for 10 s. As an internal quantitative control of the gene expression, GAPDH gene expression was determined as reported previously. [19][20][21] The aspartyl beta-hydroxylase and GAPDH gene expressions of all cDNA samples were determined by fluorescence from SYBR green using the Light Cycler software Version 3.5 (Roche Diagnostics), and the ratios of aspartyl beta-hydroxylase and GAPDH gene expressions represented the normalized relative levels of aspartyl betahydroxylase expressions. 19,22 A no-template negative control was also included in each experiment.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%